Team Based Learning Vs Problem Based Learning in Medical Education: A Systematic Review. - Gera, Mark; Rathod, Urvashi; Karra-Aly, Ayah; Aluckal, Eby; Abraham, Abe (Eastern Journal of Medical Sciences, 2023)
Purpose: Problem-based learning (PBL) has been widely used in medical education since the 1960s. In recent years, Team-based learning (TBL) has gained popularity and has been applied in various medical and other professional institutions around the world. The objective of this systematic review was to identify which teaching pedagogy, TBL or PBL, is more effective in delivering medical education. Method: The authors searched PsycNet, ERIC and PubMed databases for articles on TBL and PBL in regards to medical education, published between 2002 and 2020. The articles were selected and reviewed by the PRISMA framework guidelines. Results: The authors identified 15 articles after full-text screening that satisfied their inclusion criteria. Of the 15 articles, 12 incorporated a modified TBL format, while 3 described classic PBL. Conclusions: Overall, the majority of the articles demonstrated a positive learning experience of TBL programs. There are pros and cons to both TBL and PBL. The advantages include promoting critical thinking and fostering collaboration, while disadvantages are lack of motivation and poor clinical problem solving. In the future, finding a way to merge both of these teaching methods might optimize learning experiences in medical education.